National Curriculum Matrix as Theoretical-Methodological Orientation: The case of the Federal Highway Police - Rigo, João André; Nunes, Carlos Francisco Oliveira; Rigo, Franciele Vitali; Muller, Isabela Regina Fornari; Freire, Patrícia de Sá (Seven Editora, 2024)
The present work contextualizes the emergence of the National Curriculum Matrix (MCN) in the scenario of public security policies elaborated since the 2000s in Brazil. Based on this contextualization and considering the complexity of police work, the MCN emerged as a theoretical and methodological framework aimed at the professional training of state police (military and civil) and military firefighters. If these institutions were necessarily linked to the MCN, what about the influence of the MCN in a police institution that is not linked and has federal coverage? To answer this question, this paper analyzes, through a case study, the influence of the MCN on the Federal Highway Police – PRF. DOI:https://doi.org/10.56238/sevened2024.009-004